Rzeczpospolita Polska a współczesne wyzwania (globalnego) terroryzmu. Przyczynek do zrozumienia relacji terroryzmu, polityki i (edukacji dla) bezpieczeństwa - Małysz, Zbigniew (Kultura-Społeczeństwo-Edukacja, 2021)
This article is a combination of reporting and analysis, constituting a relatively innovative approach in the scientific literature. It combines a report on a science-topical conference with the author’s attempt to weigh up and analyse the 16 years (as of 2017 – Z.M.) of the “war on terror” in terms of security (both external and internal) and the Republic of Poland’s raison d’état with particular emphasis on what are termed “contemporary challenges and threats”, dynamically occurring in the so-called “broad security environment” (in the perspective of Central and Eastern Europe vs. the EU and NATO) (see: Summary and Conclusions). The author has used his own holistic analytical-synthetic and predictive method in accordance with the analytical paradigm proposed by Col. dr hab. Mirosław Banasik (Ph.D.), professor at UJK (Jan Kochanowski University in Kielce, Poland) (2018 – see especially: p. 13).